Differences in Developmental Functioning Profiles Between Male and Female Preschoolers Children With Autism Spectrum Disorder. Issue 9 (13th April 2020) - Craig, Francesco; Crippa, Alessandro; De Giacomo, Andrea; Ruggiero, Marta; Rizzato, Veronica; Lorenzo, Alessandro; Fanizza, Isabella; Margari, Lucia; Trabacca, Antonio
Abstract: This study investigated differences in clinical symptoms and developmental functioning profiles as well as sex‐specific correlations of clinical characteristics and communication abilities, motor skills, and maladaptive behaviors in male and female preschoolers with autism spectrum disorder (ASD). Fifty‐two females (mean age 4.5 ± 2.16 years old) and 62 males (mean age 4.2 ± 1.17 years old) with ASD were enrolled and assessed by measures including the Autism Diagnostic Observation Schedule‐Second Edition (ADOS‐2) and Psychoeducational Profile‐Third Edition (PEP‐3). We found intellectual disability in 91.2% of the children. While preschoolers with ASD showed comparable severity of restricted and repetitive behaviors ( P = 0.17), females with ASD were less severely affected than age and intelligence quotient‐matched males with ASD in the ADOS‐2 social affect domain ( P value = 0.001) and calibrated severity scores ( P = 0.002). Interestingly, sex‐specific linear regressions revealed that fine motor skills were predictive of impaired social affect in males but not in females. Specifically, motor skills might be the core feature for sex differences in ASD. Although preliminary, this finding suggests the need for more sex‐specific diagnostic and intervention strategies in order to improve early identification efforts and specific intervention targets. Lay Summary: Little is known about differences in developmental and functional profiles in males and females with autism spectrum disorder (ASD). We found important similarities and differences in the core ASD symptoms between male and female preschoolers. In addition, fine motor skills seem to predict social affect impairment and ASD symptom severity in males with ASD. Autism Res 2020, 13: 1537–1547 . © 2020 International Society for Autism Research, Wiley Periodicals, Inc.